2009
DOI: 10.1186/1477-9560-7-11
|View full text |Cite
|
Sign up to set email alerts
|

Plasma TF activity predicts cardiovascular mortality in patients with acute myocardial infarction

Abstract: Objectives and Background: Tissue factor (TF) contributes to thrombosis following plaque disruption in acute coronary syndromes (ACS). Aim of the study was to investigate the impact of plasma TF activity on prognosis in patients with ACS. Methods and Results:One-hundred seventy-four patients with unstable Angina pectoris (uAP) and 112 patients with acute myocardial infarction (AMI) were included with a mean follow up time of 3.26 years. On admission, plasma TF activity was assessed. Patients were categorized i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 35 publications
(29 reference statements)
1
29
0
Order By: Relevance
“…Encryption/decryption appears primarily to be a function of membrane microenvironment. When TF is present on the plasma membrane in an encrypted form it can still bind FVII but only acts as a cytokine receptor capable of transmitting intracellular signals and cannot activate Factor X [50-52]. Decryption leads to activation of the ability to cleave Factor X and subsequent procoagulant activity, and occurs after cell exposure to various agents [53-55].…”
Section: Regulation Of Tf Expression and Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Encryption/decryption appears primarily to be a function of membrane microenvironment. When TF is present on the plasma membrane in an encrypted form it can still bind FVII but only acts as a cytokine receptor capable of transmitting intracellular signals and cannot activate Factor X [50-52]. Decryption leads to activation of the ability to cleave Factor X and subsequent procoagulant activity, and occurs after cell exposure to various agents [53-55].…”
Section: Regulation Of Tf Expression and Activitymentioning
confidence: 99%
“…For example, TF activity increases after cell exposure to freeze-thaw cycles, calcium ionophore and phorbol myristate acetate (PMA) [56,57], stimuli that do not alter TF transcription or translation. Other factors shown to be involved in encryption/decryption include nonionic detergents, apoptosis, phosphatidyl serine exposure, lipid raft dissociation and disulfide linkage of Cysteine 186-Cysteine 209 [52,56,58,59]. Thus, regulation of gene expression, post-translational modifications and factors that regulate TF enzymatic activity may all be important in modulating TF activity in the lung.…”
Section: Regulation Of Tf Expression and Activitymentioning
confidence: 99%
“…Therefore quantitative circulating MV measurement in cardiovascular patients has been proposed as a way to generate diagnostic and prognostic information [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have also shown that the TF +5466 A/G polymorphism modulates thrombin generation initiated by vascular injury. However, other studies show no relationship between the expression of TF and increased risk of thrombus formation (Davis and Erlich, 2008;Steppich et al, 2009;Zhou et al, 2011).…”
Section: Discussionmentioning
confidence: 93%